[With regard to enemy operations on 15 and 21.12.43 on the southeast coast of Varanger Peninsula.] (1943)
Rewards available to agent search teams for canvassing the local population.; Taken from microfilm Records of the German Field Command, Armies, National Archives Series T-315,Annex 2, KTB No. 3, 210 Infantry Division, Folder 45787/3, first frame 000660. Translated by Major James F. Gebhardt, USA (retired)